Wire Wrapped Joints—A Review. (1974) - Sollars, P. M. A.
Abstract : The basic technique of wire wrapping is now well established as a simple and reliable method for joining conductor wires in a permanent, though easily replaceable, manner to more massive terminals. This paper describes the mechanical and the metallurgical basis of the joining technique and outlines the advantages. The scope of the technique as it has developed up to the present day is discussed in terms of the ranges of wrapping terminals and wrapping wires used and the types of wrapped joint that have been evolved. Finally the tools available for wire wrapping are briefly reviewed with particular emphasis on the wrapping bit.